Toni Morrison [videorecording] - Benson, Alan; Bragg, Melvyn; Morrison, Toni (Profile of a writer, 1987)
Toni Morrison who became the first African American to win the Nobel Prize in literature in 1993 discusses slavery and its appaling legacy. Reveals the true tale which inspired Morrison's Pulitzer Prize-winning nobel Beloved, the story of a mother who murders her baby rather than have her taken into slavery and is then haunted by the reincarnated child. She elaborates on the challenges of dealing with such painful material and of writing about ordinary people whose experiences seen monumentally larger than life.